Variation in initial health assessment of unaccompanied asylum-seeking children: a cross-sectional survey across England - Bhanu Williams; Behrouz Nezafat Maldonado; Alice Jane Armitage (BMJ Paediatrics Open, 2022)
Objective To assess variation in current practice of initial health assessments (IHAs) for unaccompanied asylum-seeking children (UASC) across England.Design Cross-sectional survey.Main outcomes measures Type of routine assessment carried out, threshold to specialist referrals and facilities available to complete IHA.Results Eighty-six health professionals responded across England; 47% had received training in UASC IHA and 33% in UASC mental health issues. The majority (80%) of IHAs were conducted with translator support and 7% of participants reported Child and Adolescent Mental Health Services (CAMHS) input. Around half of clinicians (53%) performed tuberculosis and bloodborne virus screening for all UASC, while other infectious diseases (IDs) screening was symptom and risk factor dependent. Overall, 14% of clinicians routinely comment on age assessment and 76% share the IHA report and health plan with UASC. The time allocated for assessment range between 30 and 90 min.Conclusion There is significant variation in practice around UASC IHAs across England, notably around CAMHS input, time allocated, translation facilities and ID screening. The results suggest that, an increase in resources available for UASC teams, improved access to specialist services and further training on UASC health are all needed. Guidance that aims to set a best practice framework for UASC IHA delivery such as a ‘one-stop shop’ model would help to standardise UASC IHA across the country.